Clinical and epidemiological characterization of influenza virus infections in children with severe acute respiratory infection in Maputo, Mozambique: Results from the implementation of sentinel surveillance, 2014 – 2016 - Nguenha, Neuza (PLoS One, 2018)
In Sub-Saharan Africa, where burden, impact, and incidence of acute respiratory infections (ARI) are the highest in the world, conversely, the epidemiology of influenza-associated severe acute respiratory infections (SARI) is incompletely known. The aim of this study was to describe the clinical and epidemiological features of influenza-associated SARI in hospitalized children in Maputo city, Mozambique. Nasopharyngeal and oropharyngeal swabs were collected from children aged 0–14 years old who met the case definition for SARI in two hospitals in Maputo city after their parents or legal representative consented to participate. A structured questionnaire was used to collect clinical and demographic data. Typing and subtyping of influenza were performed by real-time PCR. From January 2014 to December 2016, a total of 2,007 eligible children were recruited, of whom 1,997 (99.5%) were screened for influenza by real-time PCR. The median age of participants was 16.9 months (IQR: 7.0–38.9 months) and 53.9% (1076/1991) were male. A total of 77 were positive for influenza, yielding a frequency of 3.9% (77/1,991), with the highest frequency being reported in the age group 1–5 years old. Cases of influenza peaked twice each year, during which, its frequency reached up to 60%-80%. Among all influenza confirmed cases, 33.7% (26/77), 35.1% (27/77) and 28.6% (22/77) were typed as influenza A/H3N2, A/H1N1pdm09, and B, respectively. This represents the first report of influenza in urban/sub urban setting in Mozambique and the first evidence of distribution of strains of influenza in the country. Our data showed that frequency of influenza was lower than reported in a rural setting in Mozambique and the frequency of seasonal (A/H1N1pdm09) and (A/H3N2) subtypes were similar in children with SARI.